2020
DOI: 10.1186/s12889-020-09978-7
|View full text |Cite
|
Sign up to set email alerts
|

Racial discrimination and allostatic load among First Nations Australians: a nationally representative cross-sectional study

Abstract: Background Increased allostatic load is linked with racial discrimination exposure, providing a mechanism for the biological embedding of racism as a psychosocial stressor. We undertook an examination of how racial discrimination interacts with socioecological, environmental, and health conditions to affect multisystem dysregulation in a First Nations population. Methods We conducted latent class analysis (LCA) using indicators of life stress, soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…Thus, future research could explore whether reductions in selfesteem mediate relations between racism and psychopathology outcomes. Given recent evidence linking racism to allostatic load (Cave et al., 2020b) future research should also consider heightened physiological responses to racism as mediating relations with psychopathology. Last, borrowing from Indigenous models of well‐being (Gee et al., 2014) research would benefit from examining relations between exposure to racism → (dis)connection to culture → and well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, future research could explore whether reductions in selfesteem mediate relations between racism and psychopathology outcomes. Given recent evidence linking racism to allostatic load (Cave et al., 2020b) future research should also consider heightened physiological responses to racism as mediating relations with psychopathology. Last, borrowing from Indigenous models of well‐being (Gee et al., 2014) research would benefit from examining relations between exposure to racism → (dis)connection to culture → and well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, self regulation systems undergo rapid reorganization increasing youths' vulnerability to environmental stressors (Crone & Dahl, 2012; Luciana, 2013). Given that racism is associated with heightened allostatic load among Indigenous peoples (Cave et al., 2020b), race‐based stress may further tax Indigenous adolescents' already overburdened selfregulation systems. The adolescent brain is also acutely focused on social evaluation during identity development (Somerville, 2013).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Similarly, lower education and income levels are associated with higher AL and biological risk, independent of race/ethnicity or other factors ( Seeman et al, 2004 , Seeman et al, 2008 ; Beckie et al, 2012, Borrell et al, 2020 ). Thus, it is not surprising that populations of EJ and other disadvantaged communities may have increased AL and/or weakened immune responses ( Cave et al, 2020 , Dasco et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variations can also be found among studies focused on speci c groups, for instance, Indigenous people, who have been among the most widely studied in racism research [11]. National studies of mixed age groups using repeated crosssectional designs have found different rates of unfair treatment of Aboriginal or Torres Strait Islanders, including 15% in the 2012-2013 National Aboriginal and Torres Strait Islander Health Survey (NATSIHS) [23], 35% in the 2014-2015 National Aboriginal and Torres Strait Islander Social Survey (NATSISS) [24], and 37% in the 2018 Mayi Kuwayu Study [25, p. 5].…”
Section: Previous Studiesmentioning
confidence: 99%